Application of Transportation Methods in Optimizing Transportation Cost for Fleet Product Distribution - Radhiah, Radiah; Rusdiana, Siti; Marzuki, Marzuki; Saputra, T. Murdani; Mukhra, Uly Handayani (Transcendent Journal of Mathematics and Applications, 2023)
Motor vehicle distribution companies which are the source of this research data are located in Banda Aceh and Medan. The vehicles will then be sent to several areas, namely Lhokseumawe, Panton Labu, Meulaboh, Takengon, Subulussalam, Kuta Binjei, Kutacane, Aceh Singkil, Rimo and North Aceh. The problem in the process of sending vehicles is that if the inventory of vehicles in one of the warehouses is empty, then the supply of vehicles is obtained from warehouses that are still available in the warehouse regardless of distance. This paper describes the optimization of transportation costs for Fleet product distribution. Products are distributed from two sources to ten destinations. The cost of sending the vehicle incurred by the company is Rp 152,994,625. By using the Vogel's Approximation Method (VAM) and Modified Distribution Method (MODI), the total cost generated is Rp 142.728.100. Solving transportation problems with the transportation method can minimize and optimize the cost of sending a vehicle of Rp 10.266.525 or 6.71% and it can increase company profits.